Pengaruh E-Service Quality Dan E-Wom Terhadap Keputusan Pembelian Serta Implikasinya Terhadap E-Customer Loyalty Pada E-Commerce - Virgo Simamora; Syifa Fauziah (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This sresearch aims to determine the effect of e-service quality, e-wom (electronic word of mouth), purchasing decisions, and e-customer loyalty in online shopping and transactions. The rapid development of technology has a big impact on various aspects, including the business world. This research is a quantitative study using explanative type. The sampling technique uses non probability sampling and the purposive sampling approach. Where the population is all e-commerce consumers such as Shopee, Tokopedia, Lazada, BliBli.com, Bukalapak, and so forth. While the sample is 99 consumers with certain criteria. Data collection techniques using Google Form and by distributing questionnaires. This research uses the validity and reliability and path coefficients test, the results obtained from this study indicate that E-Service Quality parcially influences Purchasing Decision is not significant with insignificant value of 0.073, E-Customer Loyalty with Purchase Decision parcially influences Decision Purchases with a significant value of 0.001, and E-WOM (electronic word of mouth) Purchasing Decisions parcially affect Purchasing Decisions with a significant value of 0.003.Keyword : e-service quality, e-wom, buying decision , dan e-customer loyalt